Ruptur Perineum Grade 3A Post Trauma: Laporan Kasus - Rahma Hardiyanti; Nurul Islamy; Marzuqi Sayuti (Penerbit Goodwood, 2022)
Purpose: This study aimed to summarize the general history, physical findings, and treatment of a patient with traumatic perineal tears grade 3A. Research Methodology: A case report from Obstetrics and Gynecology RSUD Abdoel Moeloek Lampung. The subject of this study is a 9-year-old girl, hospitalized in the hospital ward with traumatic perineal tears grade 3A. Result: A 9-year-old girl complaints of vaginal bleeding after an accident 4 hours before hospitalization. On physical examination, in perineum region found vulnus laceratum regio perineum size 4 x 1 cm to external anal sphincter <50%, hymen rupture (+), bleeding and blood clot (+), rectal touch revealed anal sphincter tone (+) decreased, laceration of anal sphincter <50%. The patient was clinically diagnosed with “Traumatic Perineal Tears Grade 3A”. Definitive management is operative to repair lacerations under general anesthesia. Limitations: This case is limited to traumatic perineal tears grade 3A cases which is a rare case in children. Contribution: This article can be helpful in medical education or as a reference in making relevant case reports.